IMPLEMENTASI JIWA WIRAUSAHA DAN PEMANFAATAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWI PURWAKARTA - Ade Nurhayati (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
The research with the title of the influence of entrepreneurial spirit and the use of social media on the interest of entrepreneurship in female (case study on STIE Dr. Khez. Muttaqien and STIEB Perdana Mandiri in Purwakarta). The purpose of this study was to determine the effect of entrepreneurial spirit and the use of social media on the interest of entrepreneurship in private college students in Purwakarta. The respondent in this study were private college students in the Purwakarta economic cluster. The number of respondents in this study was determined by 95 respondents using a sampling technique called probability sampling technique. The research method used is descriptive method is a method that is carried out by collecting, presenting and analyzing data so as to provide a fairly clear picture of the object under study. This study uses a multiple linear regression analysis model with the help of IBM SPSS version 22. The results of this study shows that the variable entrepreneurial spirit and the use of social media have a positive and significant effect on the interest in entrepreneurship in female private university students in Purwakarta.